Postoperative Atrial Fibrillation and its association with the Atrial Substrate and the electrophysiological properties of the Atrial Myocardium - Osmar Antonio Centurión; Fabiola Rodríguez; Karina Scavenius; Luis Miño; Orlando Sequeira (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2017)
Postoperative atrial fi brillation (AF) has a high prevalence, affecting up to 45% of coronary artery bypass graft surgery patients within the fi rst week of the operation [1-4]. Interestingly, asymptomatic AF was reported more likely to occur after the fi rst 4 days following the cardiac surgery. Postoperative AF is associated with increased morbidity and several types of complications. It was associated with increased duration of hospitalization, with high healthcare costs, and has been associated with an increased incidence of stroke, the need for permanent pacemaker placement, and early and late mortality. Several factors were found to be associated with new-onset AF following multivariate analysis, including advanced age, higher Killip class or heart failure, hypotension, higher heart rate, history of hypertension, history of stroke, female gender, increased peak creatinine, and increased Creactive protein levels [5-9]. In addition, AF may adversely affect quality of life and is associated with a higher risk of acute heart failure, and with thromboembolic events. It has recently been demonstrated that early and late postoperative AF have different predictors [9]. Early postoperative AF is the one occurring within the first 5 days after cardiac surgery, and late postoperative AF is the one occurring between the 6 and 30 days after cardiac surgery.